2009
DOI: 10.1249/mss.0b013e3181878067
|View full text |Cite|
|
Sign up to set email alerts
|

A History of Medical Reports on the Boston Marathon

Abstract: Medical studies on the Boston Marathon not only provide lessons applicable to managing modern athletes but also demonstrate the interests and concerns of researchers who have used the event to study the physiology of prolonged exercise for more than a century.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…In contrast to the classical descriptions of the protection of organic structures such as the brain, heart and kidney during prolonged strenuous exercise, several authors have shown that after a marathon race, organs such as the heart [27] and kidney [28] are negatively affected. Therefore, the elevation of GH before the race can represent a protective mechanism of the central nervous system (CNS) [25] that can occur through a direct action of GH and by activation of the GH-IGF1 axis, according to many descriptions obtained from the literature [29,30,31,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the classical descriptions of the protection of organic structures such as the brain, heart and kidney during prolonged strenuous exercise, several authors have shown that after a marathon race, organs such as the heart [27] and kidney [28] are negatively affected. Therefore, the elevation of GH before the race can represent a protective mechanism of the central nervous system (CNS) [25] that can occur through a direct action of GH and by activation of the GH-IGF1 axis, according to many descriptions obtained from the literature [29,30,31,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…We replicated the search criteria from our previously published report [1] by using keywords "Boston Marathon" or "marathon" in PubMed and searched prior citations for additional articles. An additional search of the table of contents of the New England Journal of Medicine (NEJM) revealed no additional articles.…”
Section: Methodsmentioning
confidence: 99%
“…The Boston Marathon, organized by the Boston Athletic Association (BAA) since 1897, is the longest running annual marathon [1]. The Boston Marathon, also known as the BAA, has been used for clinical research since 1899, when two Tufts professors measured cardiac dimensions by percussion and examined urinary sediment in BAA participants [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Glucocorticoids exert their effect through the glucocorticoid receptor (GR) which is expressed in most cells of the human body and regulates the expression of multiple genes [9]. The sensitivity to glucocorticoids varies considerably between individuals [10]. Polymorphisms in the GR gene are thought to play a role in this and show associations with altered sensitivity [11].…”
Section: Introductionmentioning
confidence: 99%